2017
DOI: 10.1088/2053-1583/aa9642
|View full text |Cite
|
Sign up to set email alerts
|

Robust valley polarization of helium ion modified atomically thin MoS 2

Abstract: Atomically thin semiconductors have dimensions that are commensurate with critical feature sizes of future optoelectronic devices defined using electron/ion beam lithography. Robustness of their emergent optical and valleytronic properties is essential for typical exposure doses used during fabrication. Here, we explore how focused helium ion bombardement affects the intrinsic vibrational, luminescence and valleytronic properties of atomically thin MoS2. By probing the disorder dependent vibrational response w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 46 publications
(113 reference statements)
10
93
0
Order By: Relevance
“…5 (a) and (b) respectively. Both peaks are observed to broaden with increasing disorder and the peak positions shift as expected from previous reports 63 . Broadening begins at a substantially lower dose for Ne + than for He + as expected.…”
Section: Defect Sizessupporting
confidence: 85%
“…5 (a) and (b) respectively. Both peaks are observed to broaden with increasing disorder and the peak positions shift as expected from previous reports 63 . Broadening begins at a substantially lower dose for Ne + than for He + as expected.…”
Section: Defect Sizessupporting
confidence: 85%
“…As argued in a recent paper [20], chalcogen site defects are abundant but they can be identified as oxygen substituents rather than chalcogen vacancies with a radically different electronic structure [20,24]. Undecorated sulfur vacancies can, however, be generated by annealing or ion bombardment in vacuum as reported previously [4,10,25,26]. Calculations also showed that in vacuum, the chalcogen vacancy has the lowest formation energy of any intrinsic defect in several TMD materials [11,13].…”
mentioning
confidence: 64%
“…Room temperature PL spectroscopy reveals some information about the type and density of defects, because the intensity ratio between the A and B excitons depends on the defect density. 25 However, the doping and strain within the MoS 2 layers strongly influence the PL signal 26,27 and the defects can also enhance the PL, 28 owing to the carrier confinement around defects in the TMD layers. Furthermore, the large surface-to-volume ratio of 2D materials causes the chemisorbed 29 and physisorbed 10 molecules to significantly influence the intrinsic properties of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…As an analogy to the defect-driven phenomena imprinted in the Ramanactive modes, the defect-related PL modes are barely visible at room temperature and are only observable for very defective samples. 28 In contrast, the low-temperature PL spectra change drastically based on the sample quality. At these temperatures, the lattice defects allow an exciton to be more strongly bound to a charged or neutral defect as well as to other quasi-particles to form a bound exciton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation